GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG BAHAYA KEPUTIHAN DI DUSUN SERBA GUNA DESA KARANG REJO KECAMATAN STABAT KABUPATEN LANGKAT TAHUN 2021 - Debora Lestari Simamora (Jurnal Ilmiah Kebidanan Imelda, 2021)
Vaginal discharge is a white discharge from the vagina caused by a fungus or virus that causes itching around the vagina. This study aims to describe the knowledge of young women about the dangers of vaginal discharge in the Serba Guna Hamlet, Karang Rejo Village, Stabat District, Langkat Regency in 2021. This research is descriptive using primary data obtained by distributing questionnaires. The population in this study was mostly young women in Dusun Serbaguna Langkat in 2021 using random sampling of 30 respondents. The results of the study from 30 respondents were that the majority had less knowledge as many as 15 respondents (50%). The knowledge of respondents based on the age of the majority is less than 12-13 years as many as 8 respondents (26.6%) and the knowledge of respondents based on the majority of information sources is lacking in adolescent girls who receive information from health workers 6 respondents (20%). The conclusion of this study is that the knowledge of young women about the dangers of vaginal discharge is lacking and it is recommended to young women to maintain vaginal hygiene and to health workers to be able to provide counseling about the dangers of vaginal discharge.